Factors Related To Citing From Preceptorship Competence: A Systematic Review - Fitri Chandra Kuspita; Nursalam Nursalam; Slamet Riyadi Yuwono (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2020)
Introduction: Preceptorship is a learning method that involves more experience in conveying their knowledge to someone who is less experienced. In this article, the authors conducted a relevant systematic review in various data used the keywords “preceptorship,”transition and article thinking”. Data based on SCOPUS, Science Direct, Proquest, Pubmed, and Google Scholar. The criteria consisted of the full text published in five years limit journal (2013-2018) and used the article in English. The results as much as 1517 articles found, and selected 15 article that suitable with criteria. Aim: The purpose of this study is to analyze factors that affect the implementation of preceptorship in the hospital and to give the recommendation of monitoring and evaluation preceptorship as well. Method: Papers were critically reviewed and relevant data were extracted and synthesized using an approach based on preferred reporting items for systematic reviews and Meta-Analysis (PRISMA). Result: These factors include the level of education, experience, support, guiding model, and work environment